2005
DOI: 10.1111/j.1461-0248.2005.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

And the beak shall inherit – evolution in response to invasion

Abstract: The increased demographic performance of biological invaders may often depend on their escape from specifically adapted enemies. Here we report that native taxa in colonized regions may swiftly evolve to exploit such emancipated exotic species because of selection caused by invaders. A native Australian true bug has expanded it host range to include a vine imported from tropical America that has become a serious environmental weed. Based on field comparisons and historical museum specimens, we show that over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
208
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(213 citation statements)
references
References 38 publications
(70 reference statements)
3
208
0
2
Order By: Relevance
“…host plants (Hughes & Vogler 2004;Carroll et al 2005) exist, our results are the first to demonstrate that geographically structured coevolution can cause substantial intraspecific variation in the allometric equations of exaggerated insect traits. Therefore, our results indicate that the geographic mosaic of species interactions (Thompson 1999) provides an excellent framework for determining the trajectory of escalating coevolution.…”
Section: Scaling In Coevolutionary Arms Races H Toju and T Sota 541mentioning
confidence: 97%
“…host plants (Hughes & Vogler 2004;Carroll et al 2005) exist, our results are the first to demonstrate that geographically structured coevolution can cause substantial intraspecific variation in the allometric equations of exaggerated insect traits. Therefore, our results indicate that the geographic mosaic of species interactions (Thompson 1999) provides an excellent framework for determining the trajectory of escalating coevolution.…”
Section: Scaling In Coevolutionary Arms Races H Toju and T Sota 541mentioning
confidence: 97%
“…For example, introduced toads in Australia [14] and Chinook salmon in New Zealand [13] display adaptive evolution in dispersal and reproductive traits tied to population vital rates. Native species can also evolve quickly [9], but what remains to be seen is whether adaptive responses by natives will be sufficient to allow them to persist [67] or even flourish [68] in an increasingly homogenized global biotic community. …”
Section: Discussionmentioning
confidence: 99%
“…An alternative cause of the complex genetic population structure found in some forms of Junonia is that these species, which are defined on the basis of morphology and colour patterns, may include races that are specializing on different larval host plants. Host plant specialization is a widespread mechanism for population differentiation causing rapid evolution of adaptive traits for feeding on new hosts and for assortative mating to maintain favourable combinations of traits [109][110][111][112][113]. In some cases, it has been suggested that this has been a driver for reproductive isolation and incipient speciation in many insects [113][114][115][116][117].…”
Section: Discussionmentioning
confidence: 99%